The completeness of a normed space is equivalent to the homogeneity of its space of closed bounded convex sets - Hetman, I. (Carpathian Mathematical Publications, 2013)
We prove that an infinite-dimensional normed space $X$ is complete if and only if the space $BConv_H(X)$ of all non-empty bounded closed convex subsets of $X$ is topologically homogeneous.